Manajemen Kurikulum Manajemen Kurikulum Berbasis Drill Di Sekolah Islam Dalam Menanamkan Nilai-nilai Spiritual Siswa - Ayu Umi Salamah; Ayu Wulandari; Syunu Trihantoyo; Amrozi Khamidi; Nur Aisyah; Faruq Abdul Muid (Program Studi Manajemen Pendidikan, 2026)
The cultivation of students' spiritual values in Islamic schools requires curriculum management that not only organizes learning content, but also guides the internalization of moral values through meaningful habituation. This study aims to analyze the role of curriculum management functions, namely Planning, Organizing, Actuating, and Controlling (POAC), in instilling spiritual values consisting of moral knowing, moral feeling, and moral action among students through a drill-based curriculum. This research employed a Systematic Literature Review (SLR) using the PRISMA approach. Literature was searched in PubMed, Scopus, ScienceDirect, Taylor & Francis, Google Scholar, and SINTA with the keywords